Impact of Peer-Assisted Learning on Ultrasound. Issue 4 (December 2021) - Garvick, Sarah; Smith, Ian; Carter, Jason; El Tannir, Ziad; Gentile, Anthony; Jones, Geoff; Rogers, Lauren; Gillette, Chris
Abstract : Purpose: The aim of this study was to understand how peer-assisted learning (PAL) could be utilized by physician assistant (PA) students in an ultrasound student interest group (USIG) as a means of developing cognitive confidence and practical competence with the imaging modality. Methods: An observational study that included 3 USIG workshops was designed. Pre- and postworkshop surveys were administered. All first-year PA students, regardless of participation in the USIG workshops, were asked to complete the voluntary and anonymous surveys. Results: A statistically significant difference between those who attended at least one workshop and those who did not attend any workshops on their postworkshop scores ( p = 0.02) was seen. There was a statistically significant association between the number of workshops attended and the postworkshop difference ( p = 0.03). Conclusion: Results show that, in the context of social cognitive theory, PAL is an efficacious learning modality that enhances learner and tutor performance in ultrasound.